Library and information science: a general knowledge encyclopedia (Jaipur RBSA Publishers, 1991)
Library and Information Science Encyclopedia is an Online Encyclopedia of Library and Information Sciences. It provides articles on librarianship studies, library science, information science, information technology, information and knowledge organization, and management. The encyclopaedia includes articles on everything from traditional library terms to a vocabulary of modern avenues in information science and technology. Encyclopedia articles will include anything and everything required for an advanced study and reference on the Library and Information Science (LIS) topics, including biographies of famous librarians.
Keywords: Library science, Information science, Information technology